2019
DOI: 10.1029/2019jd030509
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Winter Responses to Nuclear War Between the United States and Russia in the Whole Atmosphere Community Climate Model Version 4 and the Goddard Institute for Space Studies ModelE

Abstract: Current nuclear arsenals used in a war between the United States and Russia could inject 150 Tg of soot from fires ignited by nuclear explosions into the upper troposphere and lower stratosphere. We simulate the climate response using the Community Earth System Model-Whole Atmosphere Community Climate Model version 4 (WACCM4), run at 2°horizontal resolution with 66 layers from the surface to 140 km, with full stratospheric chemistry and with aerosols from the Community Aerosol and Radiation Model for Atmospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
154
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(165 citation statements)
references
References 62 publications
5
154
0
6
Order By: Relevance
“…They are selected as a limiting case scenario to assess the feasibility of potential solutions to food shocks because a solution that works in such extreme circumstances could potentially be useful in shocks of any scale. This type of catastrophe could cause below freezing temperatures over much of the Northern Hemisphere during summer ( Coupe et al., 2019 ). There are a number of catastrophes that could obscure the sun, including full-scale nuclear war causing a nuclear winter from soot rising from the burning of cities.…”
Section: Introductionmentioning
confidence: 99%
“…They are selected as a limiting case scenario to assess the feasibility of potential solutions to food shocks because a solution that works in such extreme circumstances could potentially be useful in shocks of any scale. This type of catastrophe could cause below freezing temperatures over much of the Northern Hemisphere during summer ( Coupe et al., 2019 ). There are a number of catastrophes that could obscure the sun, including full-scale nuclear war causing a nuclear winter from soot rising from the burning of cities.…”
Section: Introductionmentioning
confidence: 99%
“…The season and geographic location of soot emissions could influence soot production, rainout, and lofting, yet a systematic evaluation is lacking (6,15). The size of the conflict, fuel load, smoke composition, and plume rise introduce additional uncertainties (6,8,15,17,31,47,48). Recently revised estimates of combustible material with today's larger nuclear arsenals render previous assumptions of 5 Tg soot conservative and suggest that soot production may range from 5 to 36 Tg for the India-Pakistan case (13).…”
Section: Yearmentioning
confidence: 99%
“…Nuclear warfare could have devastating impacts on millions of people, yet it has been suggested that regional or global nuclear conflict may be possible in the future (Toon et al, ). In addition to the calamitous impacts of nuclear conflict on a local level, research conducted with a range of climate models finds a global cooling in response to various conflict scenarios (Coupe et al, ; Malone et al, ; Mills et al, ; Pausata et al, ; Robock et al, ; Turco et al, ). This global cooling is driven by fires started by the nuclear weapons.…”
Section: Introductionmentioning
confidence: 99%